An industrial safety automation system using GSM technology - Subash Das, Prachuryya (2024)
The primary aim of the proposed system is to develop a compact industrial security product based on emerging GSM technology. The project parallelly aims at providing an automized platform, enhancing the application diversity. The project basically focuses on developing the protection of dangerous gas leakages (basically methane, butane, propane, L.P.G. and Carbon mono-oxide gases) which are most common gases in the industrial sector. The system also focuses on smoke detection sensor along with temperature sensor. So as to minimize industrial hazard occurring due to gas leaks and sudden temperature divergences. The proposed system will be modelled to perform on both automatic and manual controls where the former will ensure security even when employees/workers might be absent inside an industry. Further the auto-mode would ensure relay drivers, relays, and alarm along with additional motor drivers that would systematically function coolers, emergency vents, and other emergency devices connected with the loads.